2012
DOI: 10.18632/oncotarget.477
|View full text |Cite
|
Sign up to set email alerts
|

Two hits are better than one: targeting both phosphatidylinositol 3-kinase and mammalian target of rapamycin as a therapeutic strategy for acute leukemia treatment

Abstract: Phosphatidylinositol 3-kinase (PI3K) and mammalian target of rapamycin (mTOR) are two key components of the PI3K/Akt/mTOR signaling pathway. This signal transduction cascade regulates a wide range of physiological cell processes, that include differentiation, proliferation, apoptosis, autophagy, metabolism, motility, and exocytosis. However, constitutively active PI3K/Akt/mTOR signaling characterizes many types of tumors where it negatively influences response to therapeutic treatments. Hence, targeting PI3K/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 267 publications
(302 reference statements)
0
92
0
Order By: Relevance
“…The PI3K/Akt/mTOR pathway plays an important role in cell proliferation, and is thus an interesting target for the treatment of various cancers, including hematological malignancies (26). Loss of function of phosphatases, most notably PTEN, which regulate this pathway, has been demonstrated in ATL (6).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt/mTOR pathway plays an important role in cell proliferation, and is thus an interesting target for the treatment of various cancers, including hematological malignancies (26). Loss of function of phosphatases, most notably PTEN, which regulate this pathway, has been demonstrated in ATL (6).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a body of evidence suggests that constitutive activation of mTORC1 in AML is independent of PI3K which in turn can be constitutively fully activated in an mTOR-independent manner. 29 Previous studies have demonstrated that PI3K/Akt inhibitors caused decreased expression of many proteins including survivin 17,18,[30][31][32] in solid tumors and hematologic malignancies. Additionally, it has been shown in a mouse model that internal tandem duplication of Flt3 regulates survivin expression via PI3K/Akt leading to aberrant progenitor cell proliferation and promoting leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,35 The prognostic impact of the PI3K/Akt/CytSurWT pathway described in this study provides important information for the clinical management of AML patients. PI3K/Akt inhibitors (MK2206, BKM120, LY2181308) or dual PI3K/mTOR inhibitors, as well as survivin antagonists (terameprocol EM-1421, CWP232291) are currently being evaluated in clinical trials, in order to improve results obtained with conventional chemotherapy in AML 29 . As a consequence of our findings, the PI3K/Akt/CytSurWT activated pathway represents a favorable prognostic factor identifying patients likely to achieve a long-term cure with conventional chemotherapy regimens.…”
Section: Cd38mentioning
confidence: 99%
“…In mammalian cells, there are three classes of PI3Ks. Class I PI3K is an inhibitor of autophagy [79] . Class II PI3K activity is thought to have no relevance to autophagic control.…”
Section: Pi3k Inhibitorsmentioning
confidence: 99%